THE ROLE OF GOVERNMENT ASSISTANCE IN ENHANCING MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) PRODUCTIVITY - Pramuditya, Nia; Arif Musthofa, M.; Kadarsih, Sri; Fatimah, Siti (Jurnal Dinamika Ekonomi Syariah, 2025)
This study discusses three main problems, namely the role of MSME assistance in increasing the productivity of aid recipients, the process of distributing MSME assistance carried out by the Cooperatives and MSMEs Office, and the obstacles faced in distributing the assistance. This study uses a qualitative approach with primary and secondary data obtained through observation, interviews, and documentation. The study was conducted on 15 business actors who received MSME assistance in Geragai District. The results showed that 80% (13 business actors) experienced business development, while 20% (2 business actors) showed no development. The results of the analysis concluded that the role of MSME assistance was very helpful in increasing income, product quality, production capacity, profit and loss, and business performance of aid recipients. The aid distribution process was carried out according to the rules stated in the Decree (SK), involving the village and sub-district, and collecting aid recipients at the sub-district office. The main obstacle faced was inactive NIK data, so cooperation with the Dukcapil Office was needed to activate the data online. In addition, village and sub-district officials are expected to be more careful in sending data so that all aid recipients can be contacted properly.